Factors influencing the adoption of internet banking: An integration of ISSM and UTAUT with price value and perceived risk - Almaiah, Mohammed Amin; Al-Rahmi, Ali Mugahed; Alturise, Fahad; Alrawad, Mahmaod; Alkhalaf, Salem; Lutfi, Abdalwali; Al-Rahmi, Waleed Mugahed; Awad, Ali Bani (Frontiers in Psychology, 2022)
Abstract: The investigation of satisfaction and intention to use in commercial banks needs to focus specifically on internet banking, as it is the fastest-growing banking service. This paper investigates the satisfaction and behavioral intention of using Malaysian Internet Banking to use Internet Banking by focusing on the Information System Success Model (ISSM) and integrated adoption and application technology (UTAUT) theory. The important aspects are as follows: perceived Risk (PR), Facilitating Conditions (FC), Price (PV), Performance expectancy (PE), Information Quality (IQ), Service Quality (SEQ), System Quality (SQ), customer satisfaction and behavioural purpose to be applied in the Internet Banking process and their use of Online Banking. To check the idea being studied, we arranged a sample of 362 valid responses the Malaysian customers using E-Banking. The outcomes determine the relationship of customers and the factors affecting the customers’ acceptance of Online Banking. In the light of these findings, a model of research is developed called “Structural Equation Model (SEM)”. The findings show a satisfactory response from the customers using Internet Banking and this also shows a positive influence on the acceptance of the Online banking system. However, some of the clients were not completely satisfied with the perceived risk of Internet Banking. This particular research is a country specific. It provides the necessary grounds for the study of internet banking accreditation, some useful information for the practitioners, policy makers and the researchers to improve the system of online banking in the country